Antinociceptive Action of Thymoquinone-Loaded Liposomes in an In Vivo Model of Tendinopathy - Laura Micheli; Lorenzo Di Cesare Mannelli; Elena Mosti; Carla Ghelardini; Anna Rita Bilia; Maria Camilla Bergonzi (MDPI AG, 2023)
Tendinopathies represent about 45% of musculoskeletal lesions and they are a big burden in clinics characterized by activity-related pain, focal tendon tenderness and intra-tendinous imaging changes. Many approaches have been proposed for tendinopathies' management (e.g., nonsteroidal anti-inflammatory drugs, corticosteroids, eccentric exercises, laser therapy), unfortunately with very little support of efficacy or serious side effects, thus making the identification of new treatments fundamental. The aim of the study was to test the protective and pain reliever effect of thymoquinone (TQ)-loaded formulations in a rat model of tendinopathy induced by carrageenan intra-tendon injection (20 µL of carrageenan 0.8% on day 1). Conventional (LP-TQ) and hyaluronic acid (HA)-coated TQ liposomes (HA-LP-TQ) were characterized and subjected to in vitro release and stability studies at 4 °C. Then, TQ and liposomes were peri-tendon injected (20 µL) on days 1, 3, 5, 7 and 10 to evaluate their antinociceptive profile using mechanical noxious and non-noxious stimuli (paw pressure and von Frey tests), spontaneous pain (incapacitance test) and motor alterations (Rota rod test). Liposomes containing 2 mg/mL of TQ and covered with HA (HA-LP-TQ2) reduced the development of spontaneous nociception and hypersensitivity for a long-lasting effect more than the other formulations. The anti-hypersensitivity effect matched with the histopathological evaluation. In conclusion, the use of TQ encapsulated in HA-LP liposomes is suggested as a new treatment for tendinopathies.